Criminal Policy on Prevention of Child Exploitation in the Form of Donation Requests through the TikTok Platform - Larasati, Ayu; Wahyudi, Slamet Tri (Law Development Journal, 2024)
The development of digital technology, especially the TikTok social media platform, has created new loopholes for child exploitation, one of which is through the practice of requesting donations involving orphanage children. This study aims to analyze the causal factors of child exploitation on TikTok Media. Using a normative legal research method with a legislative approach and a conceptual approach, this study analyzes various legal instruments related to child protection and examines preventive efforts outside the realm of criminal law. The results of the study indicate that although criminal law instruments are available through Law No. 35 of 2014 concerning Child Protection, it is necessary to strengthen non-penal policies through multi-party collaboration between the government, social media platforms, and the community to create a more comprehensive child protection system in the digital era.